Prevalence of temporomandibular disorder symptoms in patients with rehabilitation needs at HUB/Ebserh, from 2016 to 2021 (Research, Society and Development, 2022)
Objective. To evaluate the prevalence of symptoms of Temporomandibular Disorders (TMD) in patients with rehabilitation needs, through the evaluation of medical records of patients treated at the Total Removable Prosthesis (PTR) and Partial Removable Prosthesis (PPR) undergraduate clinics and at the Dental Specialty Center (CEO) of the University Hospital of Brasília (HUB/Ebserh), from 2016 to 2021.Methodology. A survey of medical records was carried out, analyzing the following items: main complaint and reports of headaches, obtained in the anamnesis and evaluation of the temporomandibular joint in the physical examination. After surveying the medical records, the data collected were tabulated and quantitatively analyzed. Results. A total of 124 printed medical records were analyzed, among which 24 were users of PTR, 46 of PPR and 54 of PTR and PPR associated. The prevalence of TMD symptoms was 11.29% (n=14) in PTR users, 19.35% (n=24) in PPR users and 16.93% (n=21) in patients with PTR/ associated PPR, resulting in 47.58% (n=59) of all the medical records evaluated. Of this percentage, 38.70% (n=48) were female, aged between 39 and 79 years. Conclusion. According to the results obtained, the prevalence of TMD symptoms in patients with rehabilitative needs for total and/or partial removable dental prostheses was 47.58%, affecting more women (38.70%), aged 39 to 79 years.